2023
DOI: 10.1371/journal.pone.0285293
|View full text |Cite
|
Sign up to set email alerts
|

Do system quality and information quality affect job performance? The mediation role of users’ perceptions

Deddy Eduar Eka Saputra,
Vera Maulida Rahma,
Anis Eliyana
et al.

Abstract: This study aims to analyze the influence of the system quality and information quality from the Correctional Database System (CDS) on the job performance of correctional Technical Support Officers (TSO) in Sumatra, either directly or through the mediating role of perceived ease of use and perceived usefulness. This study tested 118 correctional officers selected by the purposive sampling technique. A quantitative approach is used with Partial Least Square–Structural Equation Modeling analysis technique. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Findings confirmed the significant impact of PU, PEU, and INT on the current and future Q the groups studied [ 39 ]. Similar conclusions were reached by Saputra et al [ 40 ] and Chirchir et al [ 41 ]. Souza et al [ 42 ] proposed a process model for the evaluation of the Q of clinical decision support systems following the ISO/IEC 25022 and ISO/IEC 25010 standards, part of which was to identify the effect of SAT on Q.…”
Section: Introductionsupporting
confidence: 91%
“…Findings confirmed the significant impact of PU, PEU, and INT on the current and future Q the groups studied [ 39 ]. Similar conclusions were reached by Saputra et al [ 40 ] and Chirchir et al [ 41 ]. Souza et al [ 42 ] proposed a process model for the evaluation of the Q of clinical decision support systems following the ISO/IEC 25022 and ISO/IEC 25010 standards, part of which was to identify the effect of SAT on Q.…”
Section: Introductionsupporting
confidence: 91%
“…Their research also examined the impact of system quality on perceived usefulness and perceived ease of use. Another study explained that system quality had a significant influence on perceived usefulness and perceived ease of use (Saputra et al, 2023). Thus, the hypothesis related to system quality is as follows:…”
Section: System Qualitymentioning
confidence: 99%
“…The creation of value for customers on e-commerce websites is contingent upon the quality of information, which can be assessed by several factors such as product quality, system design, and the quality of software products provided to consumers (Sharma and Lijuan, 2015). In previous studies, (Machdar, 2016;Legramante et al, 2023;Saputra et al, 2023) found that the quality of information positively affects perceived usefulness and perceived ease of use. Based on the description above, the hypothesis formulated in this study as follows:…”
Section: Information Qualitymentioning
confidence: 99%
“…Within the organizational context, detention centers and correctional institutions grapple with challenges such as overcrowding [6][7][8] and the prevalence of health issues among residents [9]. In Indonesia, detention centers and correctional institutions, in general, contend with a shortage of health facilities, medical personnel, and healthcare workers [10].…”
Section: Introductionmentioning
confidence: 99%